Efforts to Improve Outcomes Throwshoot Belajarfree At Basketball Game Through Play Approach In Grade VII Private SMP Al-Ikhwan Terrain Academic Year 2015/2016: Efforts to Improve Outcomes Throwshoot Belajarfree At Basketball Game Through Play Approach In Grade VII Private SMP Al-Ikhwan Terrain Academic Year 2015/2016 - Pedomanta Keliat (Journal of Midwifery and Nursing, 2020)
This research is a classroom action research (PTK). The research was conducted within two cycles, with each sikluster themselves on planning, action, observation, and reflection. Sources of data in this study berupates to students in the form of application of the basic techniques of basketball free throw shoot. Data collection techniques with the assessment of learning outcomes shoot basketball free throw. Teknikan alisis descriptive data used is based on a qualitative analysis by percentage. The results obtained from the initial observation that is otherwise completed 9 students (37%), while 15 other students declared incomplete (63%). In the first cycle of 17 students obtained hasildimana otherwise completed (71%), while 7 other students expressed tidaktuntas (29%).